2019
DOI: 10.1039/c8sm01539b
|View full text |Cite
|
Sign up to set email alerts
|

Temperature effects on the nanoindentation characterization of stiffness gradients in confined polymers

Abstract: Stiffness gradients in geometrically confined polymers as measured by nanoindentation are influenced by opposing roles of the polymers viscoelastic state and the degree of confinement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 34 publications
1
15
0
Order By: Relevance
“…The profiles acquired at each applied load were then translated horizontally so that the inflection point of each profile was aligned, providing a single coordinate system for all of the profiles across the graphite−rubber interface. Even though the modulus measurements are made assuming JKR contact mechanics, we believe that the scaling of the substrate effect with x and F max is effectively described by the Hertzian contact radius ( a FF ), as calculated by eq , consistent with the recent MD simulations that show the substrate effect is not affected by changes to tip−sample adhesion strength …”
Section: Resultssupporting
confidence: 82%
See 2 more Smart Citations
“…The profiles acquired at each applied load were then translated horizontally so that the inflection point of each profile was aligned, providing a single coordinate system for all of the profiles across the graphite−rubber interface. Even though the modulus measurements are made assuming JKR contact mechanics, we believe that the scaling of the substrate effect with x and F max is effectively described by the Hertzian contact radius ( a FF ), as calculated by eq , consistent with the recent MD simulations that show the substrate effect is not affected by changes to tip−sample adhesion strength …”
Section: Resultssupporting
confidence: 82%
“…This particular behavior is commonly termed as the substrate effect or “thin film effect”. The size and extent of structural effects are highly dependent on the size of the tip used and indentation depth, the relative stiffness and location , of neighboring phases relative to the indentation, the viscoelastic state, and the incompressibility of the indented material. In particle–matrix composites, the indentation measurement can be further complicated due to the shape of the particle targeted for analysis or the presence of other nearby or subsurface particles .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…23,37,58,59 Quasi-static finite-element simulations 59 of the AFM experiment assuming elastic properties of the substrate and the glassy polymer (PMMA) film indicate stiffening near the rigid substrate. Very recent molecular dynamics simulations 60 have further suggested that the stiffness gradient length scale increases with temperature from below to above the polymer glass transition. Both simulations are based on several elastic and energetic parameters for the polymer interactions with the substrate and the indenter.…”
Section: Resultsmentioning
confidence: 98%
“…Nevertheless, much less attention has been paid to the confinement of SRPs inside the spherical container, especially considering SRP mixtures with polydispersity. The physical effects from the topological constraints and confinements play significant roles in the structure and function of individual genetic materials [34][35][36][37][38], such as chromosome shape in elongated bacterial cells [39], DNA (or DNA-actin filament mixtures) self-organization in a cell-size confinement [40], and drug delivery from spherical vesicles [41,42], etc.…”
Section: Introductionmentioning
confidence: 99%